Implementasi Sistem Ekonomi Islam Terhadap Pertumbuhan Ekonomi Umat - Esa Cahaya Purnomo; Devi Virgiana Hermansyah; Insania Putri Amanda; Mutiara Madina Nur Aina; Yayat Suharyat (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to explore the opinions of classical and contemporary scholars about Makassid Sharia theory and to demonstrate the implementation in Islamic economics and Islamic psychology. Data sources for this study are books on Makassid's Sharia theory, Islamic economics and Islamic psychology written by classical and contemporary scholars. Data collection was conducted by careful reference surveys related to Makassid's Sharia theory and its practice in Islamic economics and Islamic psychology. The data analysis techniques used are descriptive and qualitative. The impact of this research makes the control of the Islamic economic system better. In this study, the application of Makassid Sharia in Islamic economics is found next in its five main purposes. Another purpose of this study is to determine the planning, organizing, implementing, and controlling community empowerment programs in Indonesia. Thus, the result to be achieved is to obtain a complete picture and explanation of how the governance of collecting and utilizing alms properly for the development of productive businesses. Keywords: : Implementation, Economy, Growth, People